2021
DOI: 10.1038/s41467-021-20946-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory dopamine- and serotonin-based endocannabinoid epoxides reciprocally regulate cannabinoid receptors and the TRPV1 channel

Abstract: The endocannabinoid system is a promising target to mitigate pain as the endocannabinoids are endogenous ligands of the pain-mediating receptors—cannabinoid receptors 1 and 2 (CB1 and CB2) and TRPV1. Herein, we report on a class of lipids formed by the epoxidation of N-arachidonoyl-dopamine (NADA) and N-arachidonoyl-serotonin (NA5HT) by epoxygenases. EpoNADA and epoNA5HT are dual-functional rheostat modulators of the endocannabinoid-TRPV1 axis. EpoNADA and epoNA5HT are stronger modulators of TRPV1 than either … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 69 publications
(107 reference statements)
1
6
0
Order By: Relevance
“…Based on the presented results, it may be concluded that in stromal cells from ectopic endometrium of ovarian cysts, NADA cytotoxicity is characterized by a typical CB1-mediated apoptosis pathway [ 44 ], including downstream ceramide and ROS production leading to caspase-9/-3 activation and mitochondrial dysfunction. Taken together with the previous findings on the NADA pronounced analgesic and anti-inflammatory effects [ 19 , 45 ] and our data on the higher NADAs specificity to stromal cells from endometriotic ovarian cysts, these properties may be considered as a positive factor for further research of these compounds as possible therapeutic agents for endometriosis treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Based on the presented results, it may be concluded that in stromal cells from ectopic endometrium of ovarian cysts, NADA cytotoxicity is characterized by a typical CB1-mediated apoptosis pathway [ 44 ], including downstream ceramide and ROS production leading to caspase-9/-3 activation and mitochondrial dysfunction. Taken together with the previous findings on the NADA pronounced analgesic and anti-inflammatory effects [ 19 , 45 ] and our data on the higher NADAs specificity to stromal cells from endometriotic ovarian cysts, these properties may be considered as a positive factor for further research of these compounds as possible therapeutic agents for endometriosis treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The endocannabinoid N-arachidonoyl-dopamine (NADA), which is highly expressed in the striatum, hippocampus, and cerebellum, activates TRPV1, induces the release of substance P and calcitonin gene-related peptide from dorsal spinal cord slices, and enhances hippocampal paired-pulse depression [380]. NADA and its epoxide metabolites also act as an agonist for the CB1 and CB2 receptors and show anti-inflammatory activities [337,[381][382][383]. Other dopamine-related endocannabinoids include N-oleoyldopamine (OLDA), N-palmitoyldopamine (PALDA), and N-stearoyldopamine (STEARDA) [384].…”
Section: Other Endocannabinoids and Endocannabinoid-like Compoundsmentioning
confidence: 99%
“…Our previous publication suggested that the transient receptor potential cation channel subfamily V member 1 (TRPV1), a Ca 2+ permeable ion channel, including related molecules, was increased in the inflamed mice DRG and SC. Thus, TRPV1 and associated molecules were reported as inflammatory biomarkers in both peripheral sites and the brain 19 , 39 . In this study, we showed that pCaMKIIα and related nociceptive molecules were all increased in the CFA-induced inflammatory pain model.…”
Section: Discussionmentioning
confidence: 99%